Prospective Randomized Study of Objective and Subjective Clinical Results Between Double-Bundle and Single-Bundle Anterior Cruciate Ligament Reconstruction. (April 2016) - Sasaki, Shizuka; Tsuda, Eiichi; Hiraga, Yasuharu; Yamamoto, Yuji; Maeda, Shugo; Sasaki, Eiji; Ishibashi, Yasuyuki
Background: There is controversy as to whether double-bundle anterior cruciate ligament (ACL) reconstruction with hamstring tendon graft (DB-HT) or single-bundle ACL reconstruction with patellar tendon graft (SB-PT) obtains the best clinical outcomes. Purpose: To compare the short-term clinical outcomes of DB-HT with those of rectangular-tunnel SB-PT (RTSB-PT) at 2-year follow-up and to identify the factors that affect subjective knee functional score. Study Design: Randomized controlled trial. Level of evidence, 1. Methods: Sixty-three male patients (mean age, 26.1 years) and 87 female patients (mean age, 25.8 years) were included in this study and were randomly distributed to either the DB-HT (n = 76) or RTSB-PT (n = 74) group. Clinical outcomes (knee flexion range of motion [ROM], heel-height difference, side-to-side difference in anterior laxity, rotational laxity, and Tegner activity score) were compared between the DB-HT and RTSB-PT groups, and examination of factors affecting subjective outcomes (Knee Injury and Osteoarthritis and Outcome Score [KOOS] results) was performed by multiple linear regression analysis. Results: Fourteen patients (9 DB-HT, 5 RTSB-PT) had secondary ACL injury within 2 years after primary ACL reconstruction and were excluded from analysis. In the examination of 136 patients at the 24-month follow-up, there was no significant difference between the 2 groups in clinical or subjective outcomes. The normalized knee extensor strength of the RTSB-PT group showed negative surgical technique effect in the early postoperative phase ( P = .005), but there was no significant difference between the 2 groups at the 24-month follow-up ( P = .114). There was no significant difference in change of normalized knee flexor strength between the 2 groups ( P = .493). Age, sex, body mass index (BMI), and presence of meniscus injury were the factors that affected KOOS subscale scores. Conclusion: In this prospective randomized controlled study, there was no significant difference in the incidence of secondary ACL injury and no difference in objective or subjective outcomes between the DB-HT and RTSB-PT reconstruction at 24-month follow-up. Age, sex, presence of meniscus injury, and BMI affected subjective KOOS subscale scores, while surgical technique did not.